2008
DOI: 10.1007/s00441-008-0653-1
|View full text |Cite
|
Sign up to set email alerts
|

Characteristics of retinal stem cells from rat optic cup at embryonic day 12.5 (tailbud stage)

Abstract: Photoreceptor loss causes irreversible blindness in many retinal diseases. Repair of such damage by cell transplantation is one of the most feasible types of central nervous system treatment. Retinal stem cells (RSC) are a substrate for cell-replacement therapy, and previous studies have shown that RSCs from different developmental stages have distinct properties in proliferative capacity and differentiation potential. The tailbud stage is of special interest in retinogenesis, because RSCs commence differentia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2011
2011
2012
2012

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 42 publications
(63 reference statements)
0
1
0
Order By: Relevance
“…We have found that these cells have the ability to differentiate into rhodopsin-positive cells and restore the function of degenerated retinae. 10,11 However, there is not enough background knowledge concerning the effects of transplantation directly aimed at rescuing the remaining cones.…”
Section: Introductionmentioning
confidence: 98%
“…We have found that these cells have the ability to differentiate into rhodopsin-positive cells and restore the function of degenerated retinae. 10,11 However, there is not enough background knowledge concerning the effects of transplantation directly aimed at rescuing the remaining cones.…”
Section: Introductionmentioning
confidence: 98%